Analisis Data Penel Pengaruh Umr, Nilai Output, Unit Usaha Dan Investasi Terhadap Penyerapan Tenaga Kerja Pada Sektor Industri Besar Dan Sedang Di Jawa Tengah Tahun 2011-2013 - Jaunita, Tota; , Muhammad Arif, SE. Mec. Dev (2016)
This study entitled " UMR effect panel data analysis, and the output value of the business unit in the labor market in large and medium industries in Central Java in 2011-2013". The objective is to analyze the conditions of employment of large and medium industries, the effect of the minimum wage, the output value, total value of effort and investment on the absorption of energy in Central Java in 2011-2013. The dependent variable in the form of the workforce (TK) , while the independent variables such as the minimum wage (UMR), the output value (Q), the number of business units (COMP), and investments (INV). This study uses secondary data with panel data regression analysis techniques. The result showed that the Fixed Effects Model (FEM) is a npanel data regression model is most appropriate. Based on test validity or the effect of the t test, the minimum wage and investment has no significant effect on employment, while the value of output and the number of business units significant positive effect on employment. Based on the test F. the minimum wage, the value of output, the number of business units and investments silmutan or together have an effect on employment.